Antimony sulfide as a light absorber in highly ordered, coaxial nanocylindrical arrays: preparation and integration into a photovoltaic device. Issue 11 (21st March 2015) - Wu, Yanlin; Assaud, Loïc; Kryschi, Carola; Capon, Boris; Detavernier, Christophe; Santinacci, Lionel; Bachmann, Julien
<x xml:space="preserve">Abstract</x> Functional 'extremely thin absorber' solar cells consisting of parallel, nanocylindrical, concentric p-i-n heterojunctions are prepared by atomic layer deposition.